2010
DOI: 10.3174/ajnr.a2244
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Permeability Assessed by Perfusion CT Predicts Symptomatic Hemorrhagic Transformation and Malignant Edema in Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE: SHT and ME are feared complications in patients with acute ischemic stroke. They occur Ͼ10 times more frequently in tPA-treated versus placebo-treated patients. Our goal was to evaluate the sensitivity and specificity of admission BBBP measurements derived from PCT in predicting the development of SHT and ME in patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 41 publications
3
102
1
5
Order By: Relevance
“…Computed tomography has the advantage over MRI in that the studies can be performed more rapidly, allowing measurements to be made in acute stroke before treatment with tPA (tissue plasminogen activator). In one study, CT showed disruption of the BBB in the early stages of stroke, which was proposed as an aid in deciding when it was safe to give tPA, which has a risk of inducing hemorrhage (Hom et al, 2011). Another CT study showed that increased permeability indicated a higher risk for hemorrhagic transformation and suggested that it could be used to select patients for hemicraniectomy ( Figure 2) (Bektas et al, 2010).…”
Section: Neuroimaging Of the Neurovascular Unitmentioning
confidence: 99%
“…Computed tomography has the advantage over MRI in that the studies can be performed more rapidly, allowing measurements to be made in acute stroke before treatment with tPA (tissue plasminogen activator). In one study, CT showed disruption of the BBB in the early stages of stroke, which was proposed as an aid in deciding when it was safe to give tPA, which has a risk of inducing hemorrhage (Hom et al, 2011). Another CT study showed that increased permeability indicated a higher risk for hemorrhagic transformation and suggested that it could be used to select patients for hemicraniectomy ( Figure 2) (Bektas et al, 2010).…”
Section: Neuroimaging Of the Neurovascular Unitmentioning
confidence: 99%
“…[7][8][9][10][11] In stroke patients, BBB dysfunction is associated with increased risk of secondary hemorrhage and cerebral edema, further compromising perfusion because of vasospasms or through increased intracranial pressure. 2,7,12,13 However, the spatiotemporal dynamics and mechanisms underlying vascular alterations and the potential link between BBB opening, neurovascular dysfunction and cellular injury after stroke are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…12 Ongoing effort to find predictors of HT has yielded various factors, including the etiology of stroke, extent of infarction on initial CT, increasing stroke severity (NIHSS score), increasing age, congestive heart failure, high glucose levels, and blood pressure on presentation. 11,[13][14][15][16][17] Serum markers such as matrix metalloproteinase-9 levels 18 ; imaging modalities such as CT, 19 SPECT, 20 MR imaging, 21 diffusion-and perfusion-weighted MR imaging 22 ; and blood-brain barrier permeability measures on CTP 23 are also under investigation to formulate predictive models for HT.…”
mentioning
confidence: 99%